2018
DOI: 10.1098/rspb.2018.0376
|View full text |Cite
|
Sign up to set email alerts
|

‘Green incubation': avian offspring benefit from aromatic nest herbs through improved parental incubation behaviour

Abstract: Development of avian embryos requires thermal energy, usually from parents. Parents may, however, trade off catering for embryonic requirements against their own need to forage through intermittent incubation. This dynamically adjusted behaviour can be affected by properties of the nest. Here, we experimentally show a novel mechanism by which parents, through incorporation of aromatic herbs into nests, effectively modify their incubation behaviour to the benefit of their offspring. Our study species, the Europ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 52 publications
(130 reference statements)
0
18
0
Order By: Relevance
“…Incubating females were more active later in the day suggesting that females benefit by self-feeding more, and being more active, just prior to fasting associated with night-time incubation which can involve increased energy demand (de Heij, van der Graaf, Hafner, & Tinbergen, 2007). An alternative explanation is that lower overall levels of early morning activity are associated with constraints of incubation with females delaying leaving the nest until ambient temperature has increased so that eggs cool less, decreasing subsequent rewarming effort (H. Gwinner, Capilla-Lasheras, Cooper, & Helm, 2018). However, this is not consistent with our finding that incubating females first left their nests earlier in the morning than chick-rearing females (see below).…”
Section: Discussionmentioning
confidence: 99%
“…Incubating females were more active later in the day suggesting that females benefit by self-feeding more, and being more active, just prior to fasting associated with night-time incubation which can involve increased energy demand (de Heij, van der Graaf, Hafner, & Tinbergen, 2007). An alternative explanation is that lower overall levels of early morning activity are associated with constraints of incubation with females delaying leaving the nest until ambient temperature has increased so that eggs cool less, decreasing subsequent rewarming effort (H. Gwinner, Capilla-Lasheras, Cooper, & Helm, 2018). However, this is not consistent with our finding that incubating females first left their nests earlier in the morning than chick-rearing females (see below).…”
Section: Discussionmentioning
confidence: 99%
“…The spotless starling uses unpigmented feathers and aromatic plants to enhance antimicrobial protection and nestling survival (Ruiz-Castellano et al, 2018). The European starling adds aromatic herbs to their nests that improve nestling condition through stimulating higher parent attendance and longer incubation bouts (Gwinner et al, 2018).…”
Section: Nest Lining and Compositionmentioning
confidence: 99%
“…Studies focusing on nestling weight found no influence of aromatic plants on nests of European starlings, 6,9,15 blue tits, 4,12,16 spotless starlings, 11 and tree swallows. 13,14 However, an increase in nestlings’ weight was observed in European starlings, 8,17,18 but no influence of aromatic plants on nestlings’ tarsus length was observed in another study, on the same species, 15 nor in spotless starlings. 11…”
Section: Introductionmentioning
confidence: 84%